Effusive eruption of Snow volcano in 2012–2016 (Chirpoi Island, Kuril islands) - A.V. Degterev; M.V. Chibisova; F.A. Romanyuk; A.V. Rybin (Вестник Камчатской региональной ассоциации "Учебно-научный центр". Серия: Науки о Земле)
In 2012–2016, Snow Volcano, located on Chirpoy Island (Black Brothers Islands, Kuril Islands), experienced a relatively rare event for the Kuril Island Arc — a collateral effusive eruption. Over a period of three and a half years, a clastic lava flow of andesitic composition poured out of a side cone on the southeastern slope of the volcano. The total area of the lava cover and the clastic material formed as a result of its subsequent destruction currently amounts to 854.1 thousand m2, including 502.1 thousand m2 on the slope of the volcano and 352 thousand m2 on the shelf adjacent to the island. Specific forms of relief were formed — lava deltas and volcanic beaches. The total volume of lava poured out as a result of the eruption amounted to ~0.043 km3. Similar eruptions on Chirpoy Island have occurred twice in historical times (the penultimate eruption occurred in 133 BP). The flows of clastic lava flows that poured out onto the adjacent shelf provided for the growth of the island landmass.